Relationships of Insulin and Intact and Split Proinsulin to Haemostatic Function in Young Men with and without Coronary Artery Disease - Båvenholm, Peter; Proudler, Anthony; Silveira, Angela; Crook, David; Blombäck, Margareta; de Faire, Ulf; Hamsten, Anders (Thrombosis and Haemostasis, 1995)
Glucose intolerance, hyperinsulinaemia, dyslipoproteinaemia and multiple disturbances of haemostatic function are characteristics of young men with premature coronary artery disease. The relations between glucose, insulin and insulin propeptides, in the fasting state, and after an oral glucose load, and haemostatic function were examined in 62 consecutive non-diabetic men with myocardial infarction before the age of 45 and in 41 age-matched healthy men. “True” hyperinsulinaemia, raised plasma concentrations of insulin propeptides, dyslipoproteinaemia, elevated plasma levels of fibrinogen, factor VII antigen (VIIag) and plasminogen activator inhibitor-1 (PAI-1) activity, and lower antithrombin activity (p <0.05-0.001) characterized the patients. PAI-1 activity was more closely associated with insulin, intact proinsulin and des 31,32proinsulin in patients than in controls, whereas the plasma levels of fibrinogen, activated factor VII (VIIa) and VIIag were stronger correlated with insulin and insulin propeptides in subjects without coronary artery disease. Very low density lipoprotein (VLDL) triglyceride was a strong determinant of VIIag and PAI-1 activity levels in both cases and controls, whereas VLDL triglyceride in controls and LDL cholesterol in patients related significantly to the plasma fibrinogen concentration. Thus, our data suggests that plasma insulin and insulin propeptides might be involved in the regulation of plasma fibrinogen concentration, factor VII level and plasma PAI-1 activity. However, apolipoprotein B-containing lipoproteins appear to influence the relationships between insulin, insulin propeptides and haemostatic factors in individuals with premature coronary artery disease.